SOCS2 Is Critical for the Balancing of Immune Response and Oxidate Stress Protecting Against Acetaminophen-Induced Acute Liver Injury - Monti-Rocha, Renata; Cramer, Allysson; Gaio Leite, Paulo; Antunes, Maísa Mota; Pereira, Rafaela Vaz Sousa; Barroso, Andréia; Queiroz-Junior, Celso M.; David, Bruna Araújo; Teixeira, Mauro Martins; Menezes, Gustavo Batista; Machado, Fabiana Simão (Frontiers in Immunology, 2019)
Acetaminophen (APAP) is usually safe when administrated in therapeutic doses; however, APAP overdose can lead to severe liver injury. APAP can cause direct hepatocyte damage, and stimulates an inflammatory response leading to oxidative stress. Supressor of Cytokine Signal-ing (SOCS) 2 modulates cytokine and growth factor signaling, and plays a role in the regulation of hepatic cellular processes. Our study evaluated the role of SOCS2 in APAP liver injury. The administration of a toxic dose (600 mg/kg) of APAP caused significant liver necrosis in WT mice. In SOCS2-/- mice, there was significantly more necrosis, neutrophil recruitment, and ex-pression of the neutrophil-active chemokine CXCL-1. Expression of proinflammatory cyto-kines, such as TNF-α and IL-6, was elevated, while expression of anti-inflammatory cytokines, IL-10 and TGF-β, was diminished. In vitro, SOCS2-/- hepatocytes expressed more p-NF-kB and produced more ROS than WT hepatocytes when exposed to APAP. SOCS2-/- hepatocytes were more sensitive to cell death in the presence of IL-6 and hydrogen peroxide. The administration of catalase in vitro and in vivo resulted in a pronounced reduction of cells/mice death and ne-crosis in the SOCS2-/- group. We have demonstrated that SOCS2 has a protective role in the liver by controlling pro-oxidative and inflammatory mechanisms induced by APAP.